The red pyramid - Riordan, Rick. (New York : Disney/Hyperion, 2010)
Brilliant Egyptologist Dr. Julius Kane accidentally unleashes the Egyptian god Set, who banishes the doctor to oblivion and forces his two children to embark on a dangerous journey, bringing them closer to the truth about their family and its links to a secret order that has existed since the time of the pharoahs.
Keywords: Adventure and adventurers -- Fiction; Voyages and travels -- Fiction; Mythology, Egyptian -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Secrets -- Fiction